Análise da ultraestrutura do espermatozoide humano após liofilização - Renata de Lima Bossi (2016)
Cryopreservation is a crucial technique for reproductive medicine, allowing the storage of surplus embryos, oocytes and sperm for future treatments. The cryoprotectants are substances that prevent ice crystals formation during the freezing process, protecting the cells, as well as lethal concentration of solutes maintaining the function of organelles.Glycerol is the most commonly used cryoprotectant in several seminal freezing techniques, such as slow freezing, rapid freezing, vitrification, freezing in empty zona pellucida. Sample storing after freezing usually is done in liquid nitrogen. Samples are stored in liquid nitrogen after freezing which leads to a high cost of maintenance, risk of cross contamination, difficulties in shipping and require large spaces for storage. Lyophilization is a technique widely used for dehydrating food products, pharmaceuticals, biotechnology products, vaccines and diagnostic biological materials. It consists in passing the solid material directly to the gaseous state - sublimation - maintaining the temperature sufficiently low under a low pressure. It has been used as an alternative to freezing since dehydration of semen does not require storage in liquidnitrogen or dry ice. Also, it represents storage cost reduction, in the long term, because less space would be needed to keep the samples. It would be possible to ship samples to worldwide without major complications and risks. Also, lyophilization led to inactivation of enveloped and non-enveloped viruses. However, studies show thatlyophilization causes damage to sperm structures. The aim of this study was to analyze the sperm ultrastructure of human semen after lyophilization using transmission electron microscopy. Four different media for lyophilization were used: Freeze medium, Sperm Freeze Medium, mHTF and EDTA. Samples were frozen in the conventionalmethod as a control. Twenty-one samples were used in the study. The analyzed parameters in fresh and freeze-dried sperm were: motility, concentration, vitality, DNA fragmentation and ultrastructure by transmission electron microscopy. The semen analysis after lyophilization demonstrated damage to the plasma membrane, acrosome, nucleus, midpiece, mitochondria, flagellum structure, microtubules, axoneme and outer dense fibers. Those damages varied according to the medium used in freeze-dried process. The lyophilized sperm demonstrated no motility and 100% DNA fragmentation. More studies are necessary in order to optimize lyophilization technique.